Understanding risk governance: Introducing sociological neoinstitutionalism and foucauldian governmentality for further theorizing - LIM, Wee Kiat (Institutional Knowledge at Singapore Management University, 2011)
This article traces the career of risk across prominent theoretical approaches by highlighting their key assumptions and premises, specifically the technical approach found in the physical sciences, and economics, psychology, and sociology in the social sciences. In each discipline, the strengths and limitations of each theoretical approach are pointed out. The discussion focuses on sociology in particular because other approaches—in treating risks as dominantly technical, psychological, or economic phenomena—tend to downplay the broader historical and socio-political context that impinges on risk construction and production, and its differential impact across society. This exploration points out that institutions play an important role in creating, managing, and distributing risks in society. After highlighting the integrated risk governance framework as a nascent practice-oriented framework, the framework is examined theoretically using sociological neoinstitutionalism and Foucault’s concept of governmentality. The conclusion elaborates the challenges of using these two bodies of knowledge to study risk governance of extreme events. Although Foucault’s concept of governmentality corrects neoinstitutional theory’s ambivalence toward power, more work needs to be done in order to reconcile their divergent intellectual commitments.